Pengujian Efek Kurs, Suku Bunga, dan Inflasi terhadap Jakarta Islamic Index - Sandi Mulyadi; Riky Soleman; Muhammad Ridho (Sekolah Tinggi Agama islam Negeri Majene, 2023)
The Jakarta Islamic Index (JII) is one of the stock indices in Indonesia that calculates the average share price index for stocks that meet sharia criteria. The three main macro-economic factors that can affect the JII are exchange rate, inflation, and interest rate variables. This study aims to determine the impact of exchange rate, inflation and interest rate variables on the Jakarta Islamic Index (JII). Time-series data for the period 2011-2021 were used in this study. The data analysis techniques used to test the effect of the relationship between variables are Vector Auto Regression (VAR) and Vector Error Correction Model (VECM). The test results found that in the short term, exchange rates, interest rates and inflation have no effect on the Jakarta Islamic Index, while in the long term, inflation has a positive effect, while exchange rates and interest rates have a negative effect on the JII. Furthermore, the Impulse Response Function (IRF) test shows that the JII responds positively to the fluctuation of all positive variables except interest rates which respond negatively.